Answer:
x = -1
Step-by-step explanation:
First, we can translate this statement to the equation
[tex]x^2-5=4x[/tex]
Subtracting 4x from both sides gives us a quadratic equation:
[tex]x^2-4x-5=0[/tex]
From here, we can factor the expression on the right to give us the equation's two solutions. The factored form will look like
[tex](x+a)(x+b)=0[/tex]
We need a + b = -4 and ab = -5, and picking a = 1 and b = -5 do the job there. Our expression factors then to (x + 1)(x - 5), giving us the equation
[tex](x+1)(x-5)=0[/tex]
And the solutions x = -1 and x = 5. Since we're only looking for the negative solution, x = -1 is the one we want.